Computer Network Security Technology Based on Java - Gao, Qi; Bai, Jinniu (Journal of physics. Conference series, 2021)
With the rapid development of Internet, network security occupies the primary position in computer technology. It is mainly to ensure the security of information, can make the information in the network safe transmission. Next, also want to prevent the invasion of soft virus infection. At present, there are many kinds of technologies to maintain network information security. Such as firewalls, anti-virus software technology, file encryption and digital signature technology. This paper describes the vulnerability of network security and the importance of maintaining its security, mainly study the role of Java in computer network security technology and its application in which, finally based on Java network security technology and some other comparison, draw its advantages.